2021
DOI: 10.3389/fcvm.2021.648265
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and Evaluation of Virtual Anticoagulation Clinic Care to Provide Incessant Care During COVID-19 Times in an Indian Tertiary Care Teaching Hospital

Abstract: Background: COVID-19 caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-II) has become a global pandemic disrupting public health services. Telemedicine has emerged as an important tool to deliver care during these situations. Patients receiving Vitamin K antagonists (VKA) require structured monitoring which has posed a challenge during this pandemic. We aimed to evaluate the impact of Virtual anticoagulation clinic (VAC), a Telehealth model on the quality of anticoagulation, adverse events, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…Telemedicine has a potentially broad application to cardiovascular disease (CVD), and it might have an important role as part of a strategy for the delivery of effective healthcare for patients with CVD, especially those with MI that is considered a leading cause of mortality and morbidity ( 7 ). Many studies showed that telemedicine is widely used in the cardiovascular field, such as in remote blood pressure (BP) monitoring ( 8 ), pre-hospital electrocardiography in the management of MI ( 9 ), monitoring of arrhythmias ( 7 ), monitoring of anticoagulant therapy ( 10 ), and regular follow-up of chronic cardiac conditions such as in heart failure and following MI or PCI, especially following the coronavirus disease 19 (COVID-19) pandemic ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Telemedicine has a potentially broad application to cardiovascular disease (CVD), and it might have an important role as part of a strategy for the delivery of effective healthcare for patients with CVD, especially those with MI that is considered a leading cause of mortality and morbidity ( 7 ). Many studies showed that telemedicine is widely used in the cardiovascular field, such as in remote blood pressure (BP) monitoring ( 8 ), pre-hospital electrocardiography in the management of MI ( 9 ), monitoring of arrhythmias ( 7 ), monitoring of anticoagulant therapy ( 10 ), and regular follow-up of chronic cardiac conditions such as in heart failure and following MI or PCI, especially following the coronavirus disease 19 (COVID-19) pandemic ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Telehealth in rural areas improves options via timely advice for decision-making. Several studies demonstrated successful implementation, continuity of care, and improved patient outcomes and satisfaction, with telehealth programs for anticoagulation care during COVID-19 [41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…In a study from India, the mean TTR significantly improved with the virtual clinic during the COVID-19 pandemic. 12 Before the pandemic, remote anticoagulation services improved the quality of anticoagulation by increasing the TTR and decreasing its variability. 13 These two studies indicate that there is ample space to improve the virtual anticoagulation services and achieve a better TTR than the actual clinics.…”
Section: Discussionmentioning
confidence: 99%